Changes in Biomechanical Properties of the Cornea and Intraocular Pressure After Myopic Laser In Situ Keratomileusis Using a Femtosecond Laser for Flap Creation Determined Using Ocular Response Analyzer and Goldmann Applanation Tonometry. Issue 3 (March 2015) - Shin, Jonghoon; Kim, Tae Won; Park, Soo Jeong; Yoon, Min; Lee, Ji Woong
Abstract : Purpose: To compare intraocular pressure (IOP) measurements before and after laser in situ keratomileusis (LASIK) using a femtosecond laser for flap creation, and to identify factors that may influence the preoperative and postoperative IOP, and the change in IOP after LASIK. Methods: Forty eyes from 20 patients who underwent treatment for myopia using a femtosecond laser for flap creation were enrolled in this study. The IOP and corneal biomechanical markers were prospectively measured preoperatively and 1 month after LASIK with Goldmann applanation tonometry (GAT) and the ocular response analyzer (ORA). Manifest refraction spherical equivalent, central corneal thickness, ablation depth, and mean corneal curvature (K reading) were also recorded. Results: After LASIK, there was a significant reduction in the IOP measurement with respect to the corneal-compensated intraocular pressure (IOPcc) (Δ=−0.67±2.07 mm Hg), Goldmann-correlated pressure (IOPg) (Δ=−3.92±2.19 mm Hg), and GAT (Δ=−2.6±2.51). Multiple regression analysis revealed that the corneal hysteresis (CH) and corneal resistance factor (CRF) are statistically significant predictors of IOPcc, IOPg, and GAT ( P <0.000). In this analysis, the preoperative manifest refraction spherical equivalent, CH, and CRF were significant predictors of ΔIOPcc (adjusted R 2 =0.401) and ΔIOPg (adjusted R 2 =0.386). The preoperative SE and central corneal thickness significantly predicted ΔGAT (adjusted R 2 =0.464). Conclusions: ORA provides a more complete measurement of IOP after LASIK with a femtosecond laser than GAT because ORA provides greater knowledge of the corneal biomechanics in terms of CH and CRF.